Conflict and Compatibility? Developmental Idealism and Gendered Differences in Marital Choice. Issue 2 (30th August 2016) - Allendorf, Keera
Abstract: Developmental idealism (DI) theory suggests that individuals who endorse DI schemas about marriage are more likely to choose their own spouses and do so for love. Such DI schemas conflict with South Asian gender schemas about marriage for women, but not for men. In turn, such conflict and compatibility may create gender differences in incorporating DI into expectations and experiences of marital choice and love in South Asia. Connections between endorsing DI as an abstract model of the world and using DI as a concrete guide for marriage may also differ by gender. Using survey data from Nepal, the author finds that men are more likely than women to expect to choose their own spouse and do so for love. Their parents' expectations show the same gender differences. Men are also more likely to choose their own spouses in practice. Connections between abstract and concrete DI are not stronger among men though.